Programação de Condições para Desenvolvimento de Comportamentos: Caracterização da produção científica brasileira de 1998-2017 - Cianca, Bruno Calábrio; Panosso, Mariana Gomide; Kienen, Nádia (Perspectivas em Análise do Comportamento, 2020)
This bibliographic review aimed to characterize the Brazilian behavioral analytical studies about Programming of Conditions for the Development of Behaviors (PCDC), based on a library of the area. Of the 110 studies retrieved, 69 were included for analysis, produced between 1998-2017 and which presented stage(s) of the PCDC process and/or theoretical-conceptual commitment to the principles of teaching programming. Studies that emphasized the teaching procedure without describing the planning process, experience reports, literature reviews without emphasis on PCDC, and books were excluded. The variables analyzed were: year of publication, authors and institutions, type of work, themes, concepts, stage of the PCDC, design, and results. The most researched themes were: Psychologist’s training/performance (27.5%), characterization of professional performance (15.9%); among the stages of PCDC, discovery of objective-behaviors (71.9) was the most frequent. Regarding the applied studies, all of them (N=15) demonstrated that the applied learning programs were efficient, and in only four their efficacy were assessed through follow-up. It is concluded that the studies are coherent with Carolina Bori propositions of first characterize which behaviors will be taught. PCDC can contribute to the production of knowledge and development of technologies for intervention in the most varied contexts that involve teaching and learning processes.